TAPETE PEDAGÓGICO: UM RECURSO DIDÁTICO PARA INTRODUZIR O ENSINO DE CIÊNCIAS E MATEMÁTICA NA EDUCAÇÃO INFANTIL - Beckmann, Ana Raquel (2021)
This study is part of the Teaching and Learning in Science and Mathematics research line of the Graduate Program in Science and Mathematics Teaching at the Franciscan University and was inspired by the intention of deepening studies related to interconnected teaching methodologies. curricular contents for learning in Early Childhood Education. Early childhood education through playfulness in the first stage of basic education in which learning takes place in interactions and games that, according to the Common National Curriculum Base, considers the learning and development of the child the five rights that are: Coexist; Play; Participate; To explore; Express; Know yourself. Therefore, considering the rights of learning and development, and the Common National Curriculum Base (BNCC) establishes the five fields of experience: The self, the other and the we; Body, Gestures and Movements; Traces, Sounds, Colors and Shapes; Listening, Speaking, Thinking and Imagination; Spaces, Times, Quantities, Relationships and Transformations, in which children can learn and develop, with each field of experience with learning and development goals defined and organized by age group. From this, the general objective of this research was delimited, to investigate the contributions of a pedagogical mat, in the Teaching of Science and Mathematics in Early Childhood Education. This study is structured as follows: introduction, theoretical foundation that describes general aspects of the Common National Curriculum Base, supporting the teaching of Early Childhood Education, methodological aspects that delimit the research methodology and the strategy for the development of this study, results and discussions and final considerations. The target audience of the research are children, aged between zero and five years and eleven months of age, from Early Childhood Education, in the municipality of Santa Maria, RS, Brazil. In this work, the didactic sequence (SD) was used as a teaching strategy, which was organized in order to contemplate the fields of experiences of Early Childhood Education as well as their learning rights. Therefore, this study provided the children with the tools they need to understand the world, as well as feel an integral and participative part of this process. Therefore, this didactic resource has the potential to be reproduced and applied in different educational contexts, as it is a product that provides the stimulus and acquisition of knowledge by the student, making them aware of the learning of science and mathematics teaching.